Trade shows worldwide an international directory of events, facilities and supplies - Connors, Martin; Dorgan, Charity Anne. (Detroit Gale Research, 1990)
Annual
Description based on the 1990 issue.
Keywords: Fairs -- Directories; Commercial products -- Directories; Commercial products -- Exhibitions; Trade and professional associations -- Directories